A migráció és a magyar migránsok jellemzői 1999 - 2011: Tendenciák és a migránsok profilja a KSH Munkaerő-felmérés adatai alapján - Ágnes Czibik; Miklós Hajdu; Nándor Németh; Zsanna Nyírő; István János Tóth; Gergely Türei (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2014)
– In this paper we use the Hungarian Central Statistical Office's Labour Force Survey to examine the rate of Hungarian inhabitants working abroad between 1999 and 2011. We also examine the characteristics of this group. A break in trend can be observed in the fourth quarter of 2009 in the rate of Hungarians with a foreign workplace. The growth of the rate has accelerated since then. Working abroad - including commuting between countries - is more frequent in the group of men and in the age group between 20 and 30 years. Considering education, vocational school and university degree make working abroad the most likely but this effect does not apply the same way in different geographical regions. In more developed regions the effect of education is stronger and the odds of working abroad are the highest for people with university degree. In less developed regions vocational training increases the most the odds of working in another country. The effect of age also differs: while in less developed regions being above the age of 40 decreases significantly the odds of working abroad, in developed regions this effect does not apply.
Keywords: C23; J61; R23; 330; migration; labour market; regional differences